Trade unions and Corporate Social Responsibility - Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2020)
Trade unions distort a profit-maximising firm's input choice. The nature of the resulting inefficiency depends on whether there are wage negotiations or there is efficient bargaining. Moreover, trade unions redistribute income and thereby affect welfare. If firms also pursue Corporate Social Responsibility (CSR) objectives, input choices may be distorted already in the absence of collective bargaining. Adopting a positive perspective, we show that CSR objectives, which induce a firm to expand production, have ambiguous wage and employment consequences in case of wage negotiations and raise employment if there is efficient bargaining. Importantly from a normative vantage point, such CSR objectives make a welfare-enhancing role of trade unions more likely in the presence of wage negotiations. The reverse is true in case of efficient bargaining.
Keywords: D60; J51; L31; M14; 330; Corporate Social Responsibility; Efficient Bargaining; Trade Unions; Wage Bargaining; Welfare